2018
DOI: 10.1186/s12989-018-0256-2
|View full text |Cite
|
Sign up to set email alerts
|

Multi-cellular human bronchial models exposed to diesel exhaust particles: assessment of inflammation, oxidative stress and macrophage polarization

Abstract: BackgroundDiesel exhaust particles (DEP) are a major component of outdoor air pollution. DEP mediated pulmonary effects are plausibly linked to inflammatory and oxidative stress response in which macrophages (MQ), epithelial cells and their cell-cell interaction plays a crucial role. Therefore, in this study we aimed at studying the cellular crosstalk between airway epithelial cells with MQ and MQ polarization following exposure to aerosolized DEP by assessing inflammation, oxidative stress, and MQ polarizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 73 publications
7
39
0
Order By: Relevance
“…We found that exposure to DEP caused a reduction in Tricellulin protein expression by six hours after exposure ( Figure 3). Importantly, the concentrations of DEP used in these experiments are comparable to those used in recent publications [17,42,43] and did not induce any detectable levels of cytotoxicity as measured by LDH release ( Figure 2C). While measurments of LDH release has been shown to be impacted by the presence of particulate matter such as TiO 2 and ame soot [44,45] due to interactions between the particles and LDH, diesel exhaust particles have been shown to have minimal impact on LDH activity [44].…”
Section: Discussionsupporting
confidence: 76%
“…We found that exposure to DEP caused a reduction in Tricellulin protein expression by six hours after exposure ( Figure 3). Importantly, the concentrations of DEP used in these experiments are comparable to those used in recent publications [17,42,43] and did not induce any detectable levels of cytotoxicity as measured by LDH release ( Figure 2C). While measurments of LDH release has been shown to be impacted by the presence of particulate matter such as TiO 2 and ame soot [44,45] due to interactions between the particles and LDH, diesel exhaust particles have been shown to have minimal impact on LDH activity [44].…”
Section: Discussionsupporting
confidence: 76%
“…We found that exposure to DEP caused a reduction in Tricellulin protein expression by six hours after exposure ( Figure 2). Importantly, the concentrations of DEP used in these experiments are comparable to those used in recent publications [17,42,43]. Previous studies in which 16HBE14o-cells were exposed to SRM 2975 showed no change in Occludin mRNA following 24 hours exposure despite a signi cant reduction in TEER [17].…”
Section: Discussionsupporting
confidence: 71%
“…For the ALI exposure, we used the PreciseInhale system in combination with the XposeALI cell exposure unit. These systems have previously been used to generate dry aerosols and expose cultured cells to palladium (Pd) NPs [20], and diesel exhaust particles [21], as well as carbonaceous model (Printex 90) NPs [22]. A general difficulty in comparing different exposure set-ups is the dose comparison [23].…”
Section: Discussionmentioning
confidence: 99%